Mediation as a Conflict-Solving Device in Collective Industrial Disputes - Keller, Berndt (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1988)
This paper is an attempt to schematize and survey those recent efforts of industrial relationists and labor economists to examine mediation within an inter-disciplinary framework.